Work senses and ways of participation: the case of a rural workers’ cooperative of Mario Lago Settlement, Ribeirão Preto (SP), Brazil (Cadernos de Psicologia Social do Trabalho, 2015)
The problem of participation in rural workers’ cooperatives has been studied by different points of view, but the results are not consensual. In any case, the literature shows different elements that contribute to the lack of real participation of workers, especially because the access to family agriculture’s public policies is conditional upon cooperatives or associations. The goal of this paper was to investigate the participation forms of rural workers into cooperatives through the analysis of the meanings attributed to work. We studied the case of a cooperative in Mario Lago Settlement, Ribeirão Preto (SP), Brazil, through observations and semi-structured interviews. We found out that the instrumental participation predominated in the group, reinforced by material, institutional and affective dependencies. The meanings given by the subjects reinforced the opinion that the way of rural development policies have been thought in country reflects the disproportionality between the daily experiences and the institutionalized cooperativism.